DISTINCTIVE ASPECTS OF THE PRINCIPLES GOVERNING THE RECOGNITION AND ENFORCEMENT OF COURT DECISIONS BETWEEN STATES - Halikulov Komoliddin Nosirovich (Bright Mind Publishing, 2025)
This study examines the distinctive aspects of the principles governing the recognition and enforcement of foreign court decisions in international law. It highlights the imperative nature of jus cogens norms, such as the principles of sovereign equality and international cooperation, which require state consent before foreign judgments can be enforced within their territories. The principle of reciprocity ensures cooperation in the absence of bilateral agreements, while sectoral principles like the interrelation of judicial processes and res judicata prevent duplication of cases and ensure the finality of decisions. The study further explores how these principles are embedded in international treaties and national legal frameworks, emphasizing their role in balancing state sovereignty with legal cooperation.
Keywords: Recognition of foreign judgments, enforcement, jus cogens, sovereign equality, international cooperation, reciprocity, judicial interrelation, res judicata, state sovereignty, legal certainty, jurisdiction, treaty obligations, comitas gentium, international judicial practice, mutual assistance, national legal systems.